The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1037/pro0000392
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy with nonreligious clients: A relational-cultural approach.

Abstract: In extant literature related to the integration of religion/spirituality (R/S) in psychotherapy, nonreligious clients are often excluded or briefly mentioned. Further, few theoretical frameworks supporting recommendations for intervention with or for conceptualization of nonreligious clients' unique experiences and presenting concerns are offered. The present article summarizes psychotherapy-relevant scholarship related to nonreligious people in the United States and offers recommendations for intervention usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Our study provides data related to unique explicit or implicit stereotypes of women atheists, specifically, psychotherapists and trainees may hold and of which they should be aware, such as interpreting atheist women’s sexual behaviors as immoral. Likewise, given expectations of Christian norms were a primary source of distress for our participants, clinicians should be aware of the ways in which they may contribute to the unwelcome infusion of faith and hegemonic Christianity into therapy, such as attributions of events to a higher power (e.g., “Everything happens for a reason”) or questions and assessments that assume religious belief/identity as the default (Abbott, 2021; Bishop, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study provides data related to unique explicit or implicit stereotypes of women atheists, specifically, psychotherapists and trainees may hold and of which they should be aware, such as interpreting atheist women’s sexual behaviors as immoral. Likewise, given expectations of Christian norms were a primary source of distress for our participants, clinicians should be aware of the ways in which they may contribute to the unwelcome infusion of faith and hegemonic Christianity into therapy, such as attributions of events to a higher power (e.g., “Everything happens for a reason”) or questions and assessments that assume religious belief/identity as the default (Abbott, 2021; Bishop, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, women in our study desired connection with other atheists but found it difficult to access other women atheists and/or fulfilling nonreligious groups. Thus, if congruent with fostering the therapeutic alliance, woman-and/ or atheist-identified therapists may choose to disclose their nonreligiousness to the benefit of the client and their therapeutic growth (Abbott, 2021).…”
Section: Practice Implicationsmentioning
confidence: 99%